The ecosystem service values simulation and driving force analysis based on land use/land cover: A case study in inland rivers in arid areas of the Aksu River Basin, China - Ling Xie; Hongwei Wang; Suhong Liu (Ecological Indicators, 2022)
The ecosystem of inland river basin is of great significance to the socio-economic stability in arid area. Therefore, to evaluate the ecosystem service values (ESVs) is necessary for monitor ecosystem changes. In this paper, the response of land use/land cover (LULC) during 1990 to 2020 in Aksu River Basin (ARB) to ESV was explored. The advanced equivalent factor which modified by biomass factor and socio-economic was used to evaluate the ESVs of the ARB. A patch-generating land use simulation (PLUS) was used to simulate the ESV spatial distribution considering the influences of temperature (TEM), precipitation (PRE), NDVI, DEM, Soil organic matter content (SOMC) and Human Activity Intensity of Land Surface (HAILS) of the ARB in 2030. The results show that the total ESV in the study area showed an increasing trend (1.63 × 1010 yuan to 5.64 × 1010 yuan) from 1990 to 2020. The grassland had the highest ESV, accounting for nearly 50% of the total ESV for the ARB. The factor detection results showed that q value had the following explanatory power to ESV: HAILS (0.332) > NDVI (0.126) > TEM (0.125) > PRE (0.108) > DEM(0.096) > SOMC(0.089)and the interaction between HAILS and PRE had an effect of 0.493 on ESV. The shape index (SI) was negatively correlated with the ESV, and the correlation coefficient was −0.794. The aggregation index (AI) and Shannon's Diversity Index (SHDI) were positively correlated with the ESV, and the correlation coefficients were 0.872 and 0.878, respectively. The simulation results showed a rapid increase in ESVs in 2030, the ESV of grassland would still be the largest, and the per unit ESV of plowland, forestland, unused land and water area would be 20131.07 yuan/km2, 64743.29 yuan/km2, 3054.21 yuan/km2, 41398.54 yuan/km2, respectively. This paper can help decision-makers achieve sustainable ecosystem service management and develop land-use strategies in inland river basins in arid oases.